Identification and differentiation of rice ferritin gene in two different chromosomes in several local Indonesian rice varieties - SHELA EMILIA PERMATASARI; ANDI SALAMAH (Society for Indonesian Biodiversity, 2024)
Abstract. Permatasari SE, Salamah A. 2024. Identification and differentiation of rice ferritin gene in two different chromosomes in several local Indonesian rice varieties. Biodiversitas 25: 2547-2555. The presence of ferritin protein in rice plants indicates a regulatory response to environmental iron stress. It prevents the destructive effects of the chain reaction resulting from Fe2+ accumulation in the cell. This study aimed to detect and identify the location of the ferritin gene (OsFER) in eight local rice varieties in Indonesia. OsFER2, as the target gene was amplified using PCR, visualized by electrophoresis, and then sequenced. The sequencing results were analyzed using DNA Baser, BioEdit, and ClustalX2. The predicted proteins were visualized using the SWISS-MODEL server, Rice Genome Annotation Project Database, and chromosome map tools. The results show that all rice varieties studied have 100% alignment similarity and OsFER characteristics on chromosome 11 at LOC_Os11g01530 and chromosome 12 at LOC_Os12g01530, which have striking differences. The complete protein structure of the complex is found on chromosome 12, while only a portion of alpha-helix ferritin is found on chromosome 11. Differences in the position of the ferritin gene at different chromosomes impact the functional changes in the ferritin protein as an iron homeostasis key role. The two genes show different characteristics and are located at different genomic positions, suggesting a potential regulatory impact on the level of iron stress resistance in Indonesian rice varieties.